Eventos arquetípicos junguianos nas organizações: um estudo no Ilê Aiyê - Silva, Cristhyane Ribeiro Martins da (2002)
In this work, a model of organization analyzes of the based on the Analytical Psychology of Carl Gustav Jung is constructed. The intended objective is to analyze proper of the organization archetypes to the archetypal process of individuation by Jung. The Theoretical Study it adds, to the constructions of Analytical Psychology, of the organization studies that mention psychic dimension of the organizations, getting as resulted the development of the following of the organization archetypes events: Birth, Infancy, Tickets and Psychic Structures of the Persona and the Shadow. The empirical analysis of these events is carried through Case Study in the Associação Cultural Bloco Carnavalesco Ilê Aiyê with qualitative research that uses of the methods of Analytical Psychology and the logic of the mythical speech to Imaginary Anthropology one of Gilbert Durand. In the Case Study, it is used technique of the half-structuralized interview and the comment for the data collection and is developed instruments based on the cited methods reference for the data analysis. Like issues, the archetypes events are analyzed theoretician and empirical, constructing the model of organizational analysis that promotes organization analyses of the symbolic organization that lead the decisions and processes that benefit to the psychic-affective development of individuals and organizations, even so either a model that demand new works of research for its mature ness.